Valuable compounds on conifers, macroalgae and halophyte species - Isca, Vera M. S. (2013)
As part of our on-going investigation on bioactive secondary metabolites, we carried out the phytochemical study of the endemic conifer Juniperus brevifolia and the macroalga Cystoseira abies-marine from Azores Islands, and also of the halophyte Salicornia ramosissima from Aveiro lagoon. This communication gives an overview on the isolation, structural characterization and bioactivity of the most interesting secondary metabolites found in these species.